Enhancing income opportunities - Verlarde, Rashiel (Institutional Knowledge at Singapore Management University, 2010)
Accelerating growth is essential for poverty reduction. As argued earlier, poverty has failed to decline significantly since the East Asian Crisis due to insufficiently dynamic growth, a high degree of income inequality that reduces the income elasticity of poverty reduction, and an apparent worsening of the income distribution. The first step toward addressing this failure is to accelerate growth, which will not be easy in the short run while the global slowdown continues to run its course. Moreover, even though the global crisis is gradually bottoming out, the post-crisis external environment is likely to be much less favorable than before, which threatens to leave the Philippine economy on a lower growth plateau in the absence of reforms. This adds further urgency to the removal of growth constraints that already existed before the crisis, and which are examined below.